2016
DOI: 10.1159/000452408
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysafflor Yellow A Promotes Angiogenesis via the Angiopoietin 1/ Tie-2 Signaling Pathway

Abstract: Background: The flowers of Carthamus tinctorius L. are widely used in traditional Chinese medicine to treat cerebrovascular and cardiovascular diseases. Hydroxysafflor yellow A (HSYA), the main constituent of C. tinctorius L. flowers, is known for its multiple biological activities. The present study investigated the effects of HSYA on angiogenesis in vitro and in a mouse hindlimb ischemia model. Methods: Using human umbilical vein endothelial cells (HUVEC) in vitro and a mouse hindlimb ischemia model in vivo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The migration and capillary-like tube formation of ECs play a key role in vascular remodeling and regeneration. 50 In this study, unexpectedly, we observed a decrease in migration of HUVECs with increasing concentrations of HANPs ( Figure 7A and B), and this trend was also observed in the experiment of tube formation ( Figure 7D and E). Our findings were in agreement with a recent study showing that HUVECs cultured on pure PLA scaffolds exhibited larger and more highly developed vascular structures compared to those on the nano-HAP-conjugated scaffolds.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The migration and capillary-like tube formation of ECs play a key role in vascular remodeling and regeneration. 50 In this study, unexpectedly, we observed a decrease in migration of HUVECs with increasing concentrations of HANPs ( Figure 7A and B), and this trend was also observed in the experiment of tube formation ( Figure 7D and E). Our findings were in agreement with a recent study showing that HUVECs cultured on pure PLA scaffolds exhibited larger and more highly developed vascular structures compared to those on the nano-HAP-conjugated scaffolds.…”
Section: Discussionsupporting
confidence: 76%
“…As depicted in Figure 2B, HUVECs' exposure to HAPs (25,50, 100 and 200 μg/mL) did not show any significant change in necrosis. Moreover, no significant difference of apoptosis was detected when incubated with np20 and m-HAP for 24 h compared to control (P.0.05); in comparison, HUVECs exposed to 100 and 200 μg/mL np80 for 24 h showed a significant increase in apoptotic rate as compared to control ( Figure 2C).…”
Section: Apoptosis and Necrosis Triggered By Hapsmentioning
confidence: 83%
“…Its antiangiogenic effect was firstly found on the chick embryo chorioallantoic membrane through inhibiting the mRNA expressions of bFGF, VEGF and VEGF‐F (flt‐1) 36. Lately, Chen et al12 found that HSYA promoted angiogenesis via the angiopoietin 1/tie‐2 signalling pathway using HUVECs in vitro and a mouse hindlimb ischaemia model in vivo. Wei et al 14.…”
Section: Discussionmentioning
confidence: 99%
“…What is worth to be mentioned is the pro‐angiogenic effect of HSYA which has been reported in different ischaemic models recently 12, 14. However, the underlying mechanisms have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation